Oxidation Stability Improvement For Jatropha Biodiesel To Meet The International Standard For Automotive Applications - Rizqon Fajar; Cahyo Setyo Wibowo; Siti Yubaidah (Scientific Contributions Oil and Gas, 2011)
Biodiesel from Jatropha oil has several advantages compared to which from Palm oil, among others better cold flow properties (lower cloud point, pour point and CFPP). However, Jatropha biodiesel has an oxidation stability that is too low (2-3 hours) so that its application in the diesel engine is not acceptable. This paper reports the effect of addition of Palm bodiesel and commercial anti-oxidant on the oxidation stability of Jatropha biodiesel. The objective of this research is to find the formulation for Jatropha biodiesel which will meet the oxidation stability determined by World Wide Fuel Charter 2009 (WWFC) of min.10 hours. The required addition of BHT into Jatropha biodiesel is more than 10000 ppm to meet the WWFC specification. The addition of BHT will decrease to less than 10000 ppm if the Jatropha biodiesel was blended with Palm biodiesel as much as 60% v/v. Addition of antioxidant should be limited to a minimum value because there are also concerns about the negative effects of antioxidants on the engine components